WARTOŚĆ ZABYTKOWA MIERZONA W METRACH. OCHRONA ZABYTKÓW W KONTEKŚCIE USTAWY O OCHRONIE ZABYTKÓW I OPIECE NAD ZABYTKAMI ORAZ PRAWA BUDOWLANEGO - Helena Jadwiszczok-Molencka (Ochrona Dziedzictwa Kulturowego, 2016)
This article explores the relations between the provisions of the Act on the Protection and Guardianship of Monuments and Sites and the Construction Law from the perspective of modern historic preservation. Particular emphasis is placed on the forms of direct historic preservation in the context of the record of historic monuments and sites, which, in spite of being mentioned in the said Act, is not referred to as a form of ‘preservation’. What is also highlighted in this article is the necessity to make amendments to legal acts pertaining to classification and categorisation of historic monuments and sites. The author of this article is of the opinion that this can be achieved only by standardizing administrative regulations and deleting contradictory regulations from legal acts.